The Effect of SMS Gateway Intervention on Increasing Knowledge in Pregnant Women with Anaemia - Dzakiyyah Anwar; Andi Faradilah; Andi Irhamnia Sakinah; Rini Fitriani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Anemia in pregnancy is one of the indirect causes of the high maternal mortality rate (MMR) in Indonesia. To prevent and overcome anemia in pregnancy, an Iron supplement tablets program (IST) is carried out. However, this Programme has yet to show tangible results. One of the challenges is a low mother's compliance to consuming IST due to a lack of knowledge. Today, Short Messaging Service (SMS) appears to be an alternative to health promotion media. Aims: This study aims to determine the effect of SMS gateway on the level of knowledge about IST consumption among pregnant women with anemia. Methods: This study is a double-blind experimental research with a Randomized Controlled Trial (RCT) design. We took anemic pregnant women at seven health centers in Makassar City who met the inclusion criteria with a total sample of 68 people (35 control and 33 intervention). Results: There was a significant difference in the mean value of pre-test and post-test knowledge levels in the intervention group that received SMS gateway (p-value = 0.047). However, there is no significant difference in the mean value of pre test and post-test knowledge between the control and intervention groups (p-value = 0.215). Conclusion: There is an effect of SMS gateway on the knowledge levels regarding IST consumption among pregnant women with anemia.